Asymmetric cultural proximity and greenfield foreign direct investment - Matteo Fiorini; Giorgia Giovannetti; Mauro Lanati; Filippo Santi (The World Economy, 2021)
This paper studies bilateral cultural preferences as an asymmetric dimension of cultural proximity and estimates their effect on greenfield foreign direct investment (FDI). We derive a gravity equation of FDI and test simultaneously the impact of both (a) the preferences of investing countries for recipients' culture and (b) recipients' preferences for the culture in the investing economies. While the role of investors' preferences can be rationalised with existing supply-side gravity theories of FDI, we propose new mechanisms to explain why recipients' preferences might matter as well. We use exports and imports of cultural goods to proxy for the two directions of cultural preferences. Our results reveal a stronger investment effect of the recipients' preferences, a channel so far understudied.
Keywords: 330; cultural proximity; gravity model; greenfield FDI